Assessment of accuracy of mercury sphygmomanometer and automated oscillometric device of blood pressure measurement in population of normal individuals - Wadhwani, Ravindra; Siddiqui, Nazeem I; Sharma, Balkishan (Asian Journal of Medical Sciences, 2018)
Background: Blood pressure (BP) measurement is the most common investigation performed nearly on all patients’ for diagnosis and treatment of hypertension. Accuracy of the measurement device is crucial for timely diagnosis.However, sphygmomanometer requires medical expertise whereas automated oscillometric device needs only careful observations in measuring BP. Aims and Objectives: The objective of the present study is to determinethe comparative accuracy of mercury sphygmomanometer and automated oscillometric device of measuring BP and the limit of agreement between the two devices. Materials and Methods: A cross-sectional study designed and carried out at MGM Medical College, Indore among 438 normal individuals. Age, weight, height, body mass index, history and BP were recorded. An average of three recording of BP measurement by both the devices was used. Results: Out of a total, 52.3% were male and 47.7% were female. Average SBP (130.78±17.31 mmHg) and DBP (86.96±10.26 mmHg) measured by automated instrument were significantly elevated than SBP (126.32±13.47 mmHg) and DBP (81.70±8.63 mmHg) by mercury sphygmomanometer while the mean differences in SBP and DBP (5.16±4.40 and 5.57±3.30 mmHg) were statistically significant (p=0.000). Hypertension reported in more patients with automated (79.0%) compared to sphygmomanometer (76.0%). Bland-Altman plots indicated a positive linear trend for BP readings between two instruments. Differences were more in SBP reading than DBP within three categories. Measurement of agreement indicated strong statistically significant (p=0.000) mutual agreement between the rate of judging hypertension by two apparatuses. The coefficient of determination for SBP (R2=0.95) and DBP (R2=0.87) were very high when manual readings compared to automated. Conclusion: Present research suggests that BP readings obtained by automated and sphygmomanometer is comparable however as compared to mercury sphygmomanometer ocillometric device gives slightly higher readings of SBP. Looking towards the simplicity of measurement and freedom from environmental toxicity automated ocillometricdevice may be recommended as a primary tool for early detection and management of high BP. Asian Journal of Medical Sciences Vol.9(5) 2018 17-24